2018
DOI: 10.1002/slct.201703019
|View full text |Cite
|
Sign up to set email alerts
|

Aminomethylanthracene Dyes as High‐Ionic‐Strength DNA‐Photocleaving Agents: Two Rings are Better than One

Abstract: This paper compares the DNA interactions of a bis 9‐aminomethylanthracene dye (2) vs. a mono‐anthracene (4) under high ionic strength conditions similar to those in the cell nucleus (∼150 mM NaCl and 260 mM KCl). The chloride salts triggered an enhancement in anthracene‐sensitized DNA photocleavage, where bis‐anthracene 2 exhibited superior DNA binding affinity, faster reaction kinetics, and higher levels of DNA damage at low‐ to sub‐micro molar dye concentrations (350 nm hν, pH 7.0). While spectroscopic and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(22 citation statements)
references
References 96 publications
0
22
0
Order By: Relevance
“…Therefore, the limited changes in the spectral profile of the gold complex suggest a different type of interaction with double-stranded DNA such as external/groove binding [ 42 ] (see also viscometric tests below). Literature data also confirm that, while hypochromic and bathochromic shifts in anthracene vibronic bands indicate the occurrence ofDNA intercalation, hypochromicity in the absence of red shifting is a characteristic of anthracene minor groove interactions [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 91%
“…Therefore, the limited changes in the spectral profile of the gold complex suggest a different type of interaction with double-stranded DNA such as external/groove binding [ 42 ] (see also viscometric tests below). Literature data also confirm that, while hypochromic and bathochromic shifts in anthracene vibronic bands indicate the occurrence ofDNA intercalation, hypochromicity in the absence of red shifting is a characteristic of anthracene minor groove interactions [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 91%
“…In previously published work, we described the synthesis of N 1 - (anthracen-9-ylmethyl)­ethane-1,2-diaminium dichloride ( 2 ) (Scheme ). Using the fluorometric, hydroxyl radical probe hydroxyphenyl fluorescein (HPF) and ROS scavengers such as sodium benzoate, we then demonstrated that this chromophore photosensitized the production of high levels of DNA-damaging hydroxyl radicals in the presence of 150 mM NaCl in combination with 260 mM KCl, salts which we used to approximate Na + and K + concentrations typical of those found in the cell nucleus. …”
Section: Resultsmentioning
confidence: 99%
“…The known compound N 1 -(anthracen-9-ylmethyl)ethane-1,2-diaminium dichloride 2 was synthesized and characterized as reported in our previous publication (Scheme 1). 30 For long-term storage, 10−15 mM stock solutions of 2 were prepared in dimethyl sulfoxide (DMSO) and kept at −20 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations